PENGUASAAN KONSEP DAN KEMAMPUAN BERTANYA SISWA PADA MATERI HUKUM NEWTON MELALUI PEMBELAJARAN INQUIRY LESSON DENGAN STRATEGI LBQ - Alfiyah Nur Jannah; Lia Yuliati; Parno Parno (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
This study was aimed to determine conceptualization and the ability to ask the students at Newton's laws in learning inquiry lesson with LBQ strategy, as well as knowing a student's response to the learning inquiry lesson with LBQ strategy. This research is a Mixed Methods embedded experimental design with 36 subjects class X MIA 6 SMA Negeri 1 Krian. Quantitative analysis is performed to determine students' mastery of concepts of data and response data of students towards learning. Qualitative analysis was conducted to determine the ability to ask the student and the student's response to learning. The results showed that: the student is able to reach the indicators of the highest achievement of the concept that the level of C6 and the majority of high school students have a mastery of concepts at the level of C5, the ability to ask students increased in every meeting where students become more confident to submit a question or opinion while following the teaching of physics, and students gave a positive response by 65.28% against the learning inquiry lesson with LBQ strategy.Penelitian ini bertujuan untuk mengetahui penguasaan konsep dan kemampuan bertanya siswa pada materi hukum Newton dalam pembelajaran inquiry lesson dengan strategi LBQ, serta mengetahui respons siswa terhadap pembelajaran inquiry lesson dengan strategi LBQ. Jenis penelitian ini adalah Mixed Methods desain embedded experimental dengan subjek 36 siswa kelas X MIA 6 SMA Negeri 1 Krian. Analisis kuantitatif dilakukan untuk mengetahui data penguasaan konsep siswa dan data respons siswa terhadap pembelajaran. Analisis kualitatif dilakukan untuk mengetahui kemampuan bertanya siswa dan respons siswa terhadap pembelajaran. Hasil penelitian menunjukkan bahwa: siswa mampu mencapai indikator tertinggi pencapaian konsep yaitu level C6 dan sebagian besar siswa SMA memiliki penguasaan konsep pada level C5, kemampuan bertanya siswa meningkat pada setiap pertemuan dimana siswa menjadi lebih percaya diri untuk menyampaikan pertanyaan maupun pendapat saat mengikuti pengajaran fisika, dan siswa memberikan respons positif sebesar 65,28% terhadap pembelajaran inquiry lesson dengan strategi LBQ.